Determination of Thin Layer Drying Characteristic of Globefish (Rastrelliger sp.) - Hawa, La Choviya; S., Sumardi H.; Sari, Elfira Puspita (Fakultas Teknologi Pertanian Universitas Brawijaya, 2009)
Globefish (Rastrelliger sp.) are frequently consumed in Indonesia. The globefish can be stored for several days. One of the processes to preserve globefish is salting and drying. The accurate prediction of the characteristics of globefish drying is important in producing high quality product. Therefore, the characteristic of globefish should be determined. This research was aimed to determine the equilibrium moisture content (Me) and the drying coefficient (k) by using the graphic method.Thin layer drying characteristics of globefish determined at temperature ranging 45, 50, and 55°C and for relative humidity of 33, 30, and 29%, with initial moisture content between 18.026 and 56.7% wet basis. The result showed that equilibrium moisture content equation of globefish at temperature 45°C was Me = [ln(1-RH)/(-8.763.10-6xT)]1/1.653 with moisture content of 20.262% dry basis, at 50°C was Me = [ln(1-RH)/(-7.418.10-6xT)]1/1.671 with moisture content of 20.085% dry basis, and at 55°C was Me = [ln(1-RH)/(-1.084.10-5xT)]1/1.564 with moisture content of 18.580% dry basis. Drying constant was 0.1385 hour-1 for temperature of 45°C, 0.1568 hour-1 for temperature of 50°C, and 0.1568 hour-1 for temperature of 55°C.Keyword: drying coefficient, thin layer, globefish